1998
DOI: 10.1021/jp982882i
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Stability of Template-Synthesized Metal Nanorod Sols in Organic Solvents

Abstract: Gold and silver nanorods of diameter 40 and 90 nm and having a variety of aspect ratios (length/diameter) were prepared using the template synthesis approach. After template synthesis, the nanorods were freed from the template membrane and dispersed in either hexafluoro-2-propanol (HFIP) or CHCl3. The stability of these nanorod sols was monitored using visible absorption spectroscopy. For both the Au and Ag nanorods (in both solvents), sols prepared from the 90-nm diameter nanorods were found to be less stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(145 citation statements)
references
References 47 publications
7
136
0
2
Order By: Relevance
“…The UV-visible spectrum of as prepared Ag/PVA nanorods showed a broad absorption band at λmax 458 nm. This characteristic peak was due to the oscillation of conduction band electrons of Ag known as the surface plasmon resonance (Cepak et al, 1998;Foss et al, 1994), (Link et al, 1999;Itakura et al, 1995;Jana et al, 2001). The position of plasmon absorption band (Khanna et al, 2005) was dependent of particle size, aspect ratio and diameter of nanorods and the broad nature of the absorption band in this case is indicative of the presence of both nanospheres and nanorods as reported in citrate reduction method (Zhou et al, 2006).…”
Section: Synthesis Of Hydroxyapatite Nanocompositessupporting
confidence: 53%
See 1 more Smart Citation
“…The UV-visible spectrum of as prepared Ag/PVA nanorods showed a broad absorption band at λmax 458 nm. This characteristic peak was due to the oscillation of conduction band electrons of Ag known as the surface plasmon resonance (Cepak et al, 1998;Foss et al, 1994), (Link et al, 1999;Itakura et al, 1995;Jana et al, 2001). The position of plasmon absorption band (Khanna et al, 2005) was dependent of particle size, aspect ratio and diameter of nanorods and the broad nature of the absorption band in this case is indicative of the presence of both nanospheres and nanorods as reported in citrate reduction method (Zhou et al, 2006).…”
Section: Synthesis Of Hydroxyapatite Nanocompositessupporting
confidence: 53%
“…The results showed that, silica modified PVP is a remarkably powerful capping agent for preparation of 1D arrangement of Ag nanoparticles and this kind of prepared inorganic/organic nanocomposite can now be developed towards optical and medicinal based applications (Elechiguerra et al, 2005;Sondi et al, 2008;Suvorova et al, 2005;Zheng et al, 2001). The broad nature of the UV -Visible absorption band at λ Max = 410 nm due to the oscillation of conduction band electrons of Ag indicated the presence of both embedded sphere and assembled nanospheres in SiO 2 modified PVP (Cepak et al,1998;Jana et al, 2001;Link et al, 1999). Transparency dependent on the Ag nanoparticle size was about 96% in the infra-red region (Fig.…”
Section: Preparation and Characterization Of Transparent Sio 2 -Ag/pvmentioning
confidence: 99%
“…The method is based on the electrochemical deposition of Au within the pores of nanoporous polycarbonate or alumina template membranes. The rods could be dispersed into organic solvents through the dissolution of the appropriate membrane followed by polymer stabilization (Cepak & Martin, 1998). The method can be explained as follows: initially a small amount of Ag or Cu is sputtered onto the alumina template membrane to provide a conductive film for electrodeposition.…”
Section: Template Methodsmentioning
confidence: 99%
“…In the present work, the shift in the λ max with the tailing of absorption to the longer wavelength can be attributed to the high dielectric constant of water (ε = 80). The particle size, aspect ratio and diameter of nanowires also plays important role in deciding the position of plasmon absorption band [37]. …”
Section: Absorption Spectroscopymentioning
confidence: 99%